Acquiring technological capabilities in wastewater treatment services for sustainable development and developing different applications in environmental services - Tran, Quang Thoa; Islam, Nazrul; Badir, Yuosre; Do, Ba Khang; Sonadezi Long Thanh Shareholding Company (Pathumthani : Asian Institute of Technology, 2009)
There has been a rapid growth in establishing industrial zones in recent year. To late 2007, Dong Nai has established 25 industrial zones with the total area of 6,912 hectares. (Source: Website www.dongnai.gov.vn - July 2008). Booming in industrialization results in increasing industrial wastewaters, which cause pollution to water sources. This has led growing demands of providing industrial wastewater treatment services and it has brought opportunities for Sonadezi Shareholder Services Company (SDV) to expand its business and get more profit. Being founded on July 2007, Sonadezi Services Company (SDV) is a subsidiary of The Corporation for Development of Industrial Zone of Bien Hoa (Sonadezi Bien Hoa) and has been designated to do business on providing industrial services, in which environmental management in industrial zones is the main service to develop other industrial services. This research focuses on identifying SDV{u2019}s organizational practices that has contributed to industrial development and strategy issues that need to enhance organizational performance. To examine the strategic issues, this research employs Porter's five forces analysis approach to assess the status and development of the company, and PEST analysis approach to identify the environmental influences on a business, and SWOT analysis approach to audit the overall strategic position of SDV{u2019}s business and environment. This research also points out two major problems that the company has faced, those are problem from process technologies and problem from human resource issues, and proposes solutions to improve performance of the company. Discussion in the conclusion part of this research focus on issues of acquiring technological capabilities for improving performance of the wastewater services, which eventually help SDV, a newly established organization to entry the market and attain competitive advantage for the development.
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration (Executive) in International Business {u2013} Management of Technology, School of Management
Keywords: Sewage -- Purification; Sustainable development; Environmental services